Implementasi Pencatatan Laporan Keuangan UMKM Berdasarkan Standar Akuntansi Keuangan-EMKM pada Kecamatan Medan Barat - Iqbal Rusli; Isra Hayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to observe the implementation of recording financial reports on a Micro, Small and Medium Entity basis (SAK EMKM) among MSMEs in West Medan District. This study used a qualitative method to collect data from interviews at three types of businesses: Ayam Penyet, Gado-gado, and Soto Ayam. This study shows that limited understanding of accounting and lack of literacy regarding SAK EMKM are the main obstacles in implementing financial reports on the basis of SAK EMKM